Parent Child Interaction Therapy (PCIT) in Family Parenting with Violence: Psycho-spiritual Perspective - Rachmah Nur Anganthi, Nisa; Syahrani, Icha (International Journal of Psychosocial Rehabilitation, 2020)
Purpose: This article aims to describe the impact of parenting with violence perpetrated by adults on family members in a psychospiritual perspective. Parental care patterns for children have a significant impact on child development. A child who is raised with a parenting model of violence will grow up with various emotional and behavioral problems.Methodology: The research design uses a qualitative approach with a single case. The main informants are children and mothers who have psychological problems. Characteristics of elementary school-aged children and experiencing parental violence in families by adults. Characteristics of mothers, experiencing domestic violence by spouses and parents.The assessment method to elaborate the conditions of families who commit violence using graphic tests, CSTS, binets, interviews, and observations. The intervention method used to deal with problems of parenting with violence is a behavioral approach with parent-child interaction therapy (Parent Child Interaction Therapy) techniques. Data analysis uses descriptive narrative analysis techniques.Results: The findings show that the impact of caregiving with violence in the family by adults in the form of ... Thus it can be concluded that caregiving with violence in the family has a psychospiritual impact on the growth and development of children, which inhibits maturity and self-exploration.Applications/Originality/Value: The need for the application of spiritual-based parent-child interaction therapy in families with psychological problems.